Differentiative peculiarities of Magic realism and Fantasy - Djabbarova Feruza (Periodica Journal, 2024)
The article deals with the issue of magic realism and investigates differentiative features of fantasy between magic realism. Fantastic and magic realism are two concepts that are frequently used in contemporary literature. Fantastic prose aims to take readers with varied skills down different ways by seamlessly combining the supernatural with the reality of our everyday world. The reader finds it interesting to distinguish between the real world and the imaginary one. As the term “Magic realism” suggests, magic, history, fantasy, and mythology are all used in it. The characters are frequently born with supernatural skills. It is frequently confused with Fantasy. Magic realism enhances writing by providing an original viewpoint for examining reality, culture, and the human condition.
Keywords: Magic realism; Fantasy; aesthetic concept